The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/cl2.1291
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inclusion on academic achievement, socioemotional development and wellbeing of children with special educational needs

Abstract: Background: Considering the rapid global movement towards inclusion for students with special educational needs (SEN), there is a surprising lack of pedagogical or didactic theories regarding the ways in which inclusive education may affect students with SEN. Group composition within the educational setting may play a role in determining the academic achievement, socio-emotional development, and wellbeing of students with SEN. Proponents of inclusion propose that segregated educational placement causes stigmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 135 publications
1
15
0
2
Order By: Relevance
“…Second, there were no differences in the reading and math skills of students with SEN in regular and special classes in Estonianlanguage schools. Similarly, it has been previously found that there may be no differences in academic skills between students with SEN in regular and special classes (Dalgaard et al, 2022;Hienonen et al, 2021;Ruijs & Peetsma, 2009). These results suggest that in crosssectional studies in Estonianlanguage schools, an inclusive or segregated classroom environ ment is not associated with student academic success.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Second, there were no differences in the reading and math skills of students with SEN in regular and special classes in Estonianlanguage schools. Similarly, it has been previously found that there may be no differences in academic skills between students with SEN in regular and special classes (Dalgaard et al, 2022;Hienonen et al, 2021;Ruijs & Peetsma, 2009). These results suggest that in crosssectional studies in Estonianlanguage schools, an inclusive or segregated classroom environ ment is not associated with student academic success.…”
Section: Resultssupporting
confidence: 57%
“…Earlier studies have shown slightly different results between class placement and academic skills of students with SEN (Dalgaard et al, 2022;Hienonen et al, 2021, Kivirähk & Kiive, 2022Krämer et al, 2021;Ruijs & Peetsma, 2009). The reasons for this can be many, such as how the learning process is organized and SEN definition, which can vary from country to country.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In fact, several reviews of the literature over the past 30 years have concluded that there is no consistent evidence for the advantage of either special education or inclusive education (Cook & Cook, 2020;Dalgaard et al, 2022;Hegarty, 1993;Hornby, 1992Hornby, , 1999Lindsay, 2007;Stephenson & Ganguly, 2021). A major source of evidence for the effectiveness of interventions in the field of education is Hattie's (2009) synthesis of meta-analyses.…”
Section: Zombie 3: Fully Inclusive Education Is Effectivementioning
confidence: 99%